Health, Height and the Household at the Turn of the 20th Century - Roy E. Bailey; Timothy J. Hatton; Kris E. Inwood (Institute for the Study of Labor (IZA), 2014)
We examine the health and height of men born in England and Wales in the 1890s who enlisted in the army at the time of the First World War. We take a sample of the army service records and use this information to find the recruits as children in the 1901 census. Econometric results indicate that adult height was negatively related to the number of children in the household as well as to the share of earners, the degree of crowding, and positively to socioeconomic class. Adding the characteristics of the local registration district has little effect on the household-level effects. But local conditions were important; in particular the industrial character of the district, local housing conditions and the female illiteracy rate. We interpret these as representing the negative effect on height of the local disease environment. The results suggest that changing conditions at both household and locality levels contributed to the increase in height and health in the following decades.
Keywords: I12; J13; N33; 330; heights of recruits; household structure; health in Britain